A carbon footprint assessment for pasture-based dairy farming systems in South Africa - Galloway, Craig; Swanepoel, Pieter A.; Haarhoff, Stephanus J. (Frontiers in Sustainable Food Systems, 2024)
Environmental impact evaluation of intensive dairy farming systems has been of growing interest recently as agriculture has several negative influences on the surrounding environment, including eutrophication, declines in biodiversity, and pollution of nearby waterbodies. Dairy production in particular is characterized by the emission of greenhouse gasses (GHG) contributing toward climate change. In this study, the carbon footprint of South African pasture-based dairy farming systems was assessed using a farm-gate life-cycle assessment (LCA) approach. A total of 82 pasture-based dairy farms across South Africa were assessed (2012–2022). The average carbon footprint across all dairy farming systems was 1.36 ± 0.21 kg CO2eq kg−1 fat- and protein-corrected milk produced (FPCM), which is higher than similar studies performed outside South Africa. Enteric fermentation had the largest influence on the carbon footprint, indicating the key role of methane as an emission source in ruminant dominated livestock systems. A difference in milk production efficiency was found between farming systems with the lowest and highest carbon footprints. Pasture-based dairy farming systems must be managed with adaptive management such as regenerative agriculture. Future research agendas should explore modeling approaches to assess the economic and environmental impact of dairy production, formulating a holistic understanding of the system dynamics while also quantifying net carbon emissions or sinks.